Rongeh: A Skin Disease in West Sumtra: Its Cultural Categories and Traditional Healing Method - Alexander Stark; Fatan Hamamah Yahaya (2015)
Very often medical anthropologist discover that traditional healers have own cultural categories in order to describe certain medical disorder. In this article the authors illustrate the case of a skin disease with the name rongeh as an exemplary case which should show the healing procedure of a traditional healer in West Sumatra. Sometimes the healing method of a doctor of Western biomedicine is ineffective which could be due to the negligence of incorporating cultural categories. The medical anthropologist tries to integrate an emic point of view of the traditional healer and enable so a new viewpoint of a disease.